2010
DOI: 10.1038/sj.bdj.2010.724
|View full text |Cite
|
Sign up to set email alerts
|

Third molar-related morbidity in deployed Service personnel

Abstract: Dental treatment for troops in combat situations is fraught with difficulty. Special consideration must be given to the management of third molars in military personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, for an ill‐prepared force, the incidence is considered to be up to five times higher. Data have shown that dental complaints requiring oral surgical support such as those related to third molar teeth represent a high proportion of the dental morbidity that presents in operationally deployed service personnel. Furthermore, the management of military personnel who require specialist oral surgical input in an operational environment may be challenging and require evacuation to distant locations to access specialist services.…”
Section: The Dds Demand For a Primary Care Oral Surgery Servicementioning
confidence: 99%
“…However, for an ill‐prepared force, the incidence is considered to be up to five times higher. Data have shown that dental complaints requiring oral surgical support such as those related to third molar teeth represent a high proportion of the dental morbidity that presents in operationally deployed service personnel. Furthermore, the management of military personnel who require specialist oral surgical input in an operational environment may be challenging and require evacuation to distant locations to access specialist services.…”
Section: The Dds Demand For a Primary Care Oral Surgery Servicementioning
confidence: 99%
“…Data analysis suggested that the most likely presentations would include periapical abscesses, sensitivity, fractured or lost restorations, fractured cusps, and pericoronitis. The data from Combes et al 8 highlighted the importance of pre-screening and prevention of pericoronitis in deployed personnel, given the challenges that impacted wisdom teeth can present even with dedicated dental teams in theatre, and this was emphasised to deploying personnel.…”
Section: Discussionmentioning
confidence: 99%
“…of which were related to pericoronitis. 13 The national institute for health and clinical excellence (NICE) guidelines state that a first episode of pericoronitis unless particularly severe, should not be considered as an indication for extraction but subsequent episodes are appropriate indications for surgery.…”
mentioning
confidence: 99%